Hubungan Sifat Reologis Adonan Terhadap Karakteristik Sensorik Produk Makanan Tepung Komposit Terigu-Sorgum - Muhammad Zakir (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2008)
Rheological characteristics of wheat-sorghum flour doughs has been investigated. The rheological properties of wheat dough were observed in the Laboratory of Quality control, PT Berdikari Sari Utama Flour Mills, Makassar. Organolepttic Test on bread made of the dough was conducted in the Laboratory of Food Processing and Chemistry, Research Institute of Cereals, Maros. Sorghum flour replaced wheat flour in the dough at substitution levels of 0, 10, 20, 30, 40 and 50%, respectively. Dough rheology was studied by extensigraph method. An interesting thing on the substitution level can be pointed out from the extensigram characteristics of the composite flour dough. Based on the R’5/E and Rm values, dough with similar baking characteristics to wheat flour dough was still obtained from composite flour until 20% substitution. The organoleptic test on the bread in terms of colour, taste, flavour and texture showed that substitution level at 20% level produced bread closely similar to wheat bread.Key words: Rheology, dough, flour composite, organoleptic, sensoric perception.